Pelatihan Pembuatan Souvenir Kreatif Sebagai Upaya Pengembangan Diri dan Pengelolaan Keuangan Anak Asuh di Yayasan Al-Kahfi - Michael Ari Sulistia Putra; Destyana Putri Arsanti; Vicky Oktavia; Almira Santi Samasta; Mochammad Eric Suryakencana Wibowo (Pusat Riset dan Inovasi Nasional, 2026)
The community service program carried out through a creative souvenir-making workshop at the Al-Kahfi Foundation was designed as an initiative to strengthen the self-development potential and financial management skills of foster children. The program focused on providing participants with practical experience in creating creative souvenir products that possess economic value, while simultaneously introducing fundamental concepts of financial literacy. These concepts included cost planning, pricing strategies, simple profit calculations, and basic financial record-keeping to help participants understand the flow of income and expenses. The implementation of the program involved several stages, such as theoretical instruction on creativity and entrepreneurship, demonstrations of souvenir production techniques, hands-on practice sessions, group-based mentoring, and evaluations of both the finished products and participants’ financial notes. The results showed notable improvements in the foster children’s creativity, independence, and self-confidence, as well as better awareness and skills in managing finances in a more organized and responsible way. Overall, this community service program was effective in integrating creative skill development with basic financial literacy, serving as an empowerment effort to prepare foster children for a more independent, productive, and sustainable future.